-26+8n=-8(-8-4n)-6n

Simple and best practice solution for -26+8n=-8(-8-4n)-6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -26+8n=-8(-8-4n)-6n equation:


Simplifying
-26 + 8n = -8(-8 + -4n) + -6n
-26 + 8n = (-8 * -8 + -4n * -8) + -6n
-26 + 8n = (64 + 32n) + -6n

Combine like terms: 32n + -6n = 26n
-26 + 8n = 64 + 26n

Solving
-26 + 8n = 64 + 26n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-26n' to each side of the equation.
-26 + 8n + -26n = 64 + 26n + -26n

Combine like terms: 8n + -26n = -18n
-26 + -18n = 64 + 26n + -26n

Combine like terms: 26n + -26n = 0
-26 + -18n = 64 + 0
-26 + -18n = 64

Add '26' to each side of the equation.
-26 + 26 + -18n = 64 + 26

Combine like terms: -26 + 26 = 0
0 + -18n = 64 + 26
-18n = 64 + 26

Combine like terms: 64 + 26 = 90
-18n = 90

Divide each side by '-18'.
n = -5

Simplifying
n = -5

See similar equations:

| 20y+7=15 | | 8x-64x^(-1/2)=0 | | 78=-6r | | g-2=(4g-2)/4 | | 9k^2-6k-9=0 | | 5e+7=17 | | 53-4x=29-3x | | 35-3x=14-10x | | 3x-24=4x-8 | | 1-3x(1)-(-3)-2(x-3)=3x-(-4) | | 2x+7=6x+19 | | (8x-64x^(-1/2)) | | -(8v-7)=25-5v | | -7f=56 | | (7x+1)(8x-6)= | | x+7=3x+9.5 | | (x^(2/3)y^(-(5/4)))^6 | | 1.4/7.7 | | lg(x^2-x-6)-lg(x-3)=0 | | 25x^2+35x=0 | | 5=-7+a | | 40=-8(x+2) | | 1.5y-2=y | | 1/2x+2/5=1/3x+3/4 | | 10*t+6*(0.8-t)=6 | | (x-16)2=64 | | 9x+20=2x+125 | | 4x-6=x-18 | | -5k-2+9k+6= | | 1/2(6x-4)-4x=3x-18 | | x^4+18x^2+17=0 | | 3x-x+1=2x+5 |

Equations solver categories